Sufficient conditions and radius problems for the Silverman class - Kumar, S. Sivaprasad; Priyanka, Priyanka (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5For $00,$ let \begin{equation}\label{1} G_{λ,α}=\left\{f\in\mathcal{A}\colon \left|\frac{1-α+α zf''(z)/f'(z)}{z f'(z)/f(z)}-(1-α)\right|